2017
DOI: 10.18378/rvads.v12i3.4538
|View full text |Cite
|
Sign up to set email alerts
|

Controle de Cosmopolites sordidus (Coleoptera:Curculionidae) com os fungos entomopatogênicos Beauveria bassiana e Metarhizium anisopliae em banana

Abstract: Resumo: O uso contínuo de agrotóxicos promove uma redução rápida e eficaz das pragas, contudo, esta prática acarreta nas pragas a possibilidade de desenvolver resistência, sujeitando o agricultor a mudar constantemente de produto, aumentar a dose ou até mesmo misturar ou usar produtos ainda mais tóxicos. Sendo Cosmopolites sordidus um coleóptero de hábitos noturnos que prejudica a bananeira, pois suas larvas abrem galerias no seu rizoma e na parte inferior do pseudocaule, acarretando em declínio, tombamento e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…According to Moreira et al (2017) successive collections of C. sordidus are important for the number of insects that are removed from the banana cultivation area. For these authors, the use of baits made from the pseudostem is also an important practice in the management of C. sordidus and can be recommended for small properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Moreira et al (2017) successive collections of C. sordidus are important for the number of insects that are removed from the banana cultivation area. For these authors, the use of baits made from the pseudostem is also an important practice in the management of C. sordidus and can be recommended for small properties.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the transmission of the pathogen was more efficient in the area with the presence of the two weevil borers and M. hemipterus contributed to the spread of B. bassiana in the population of C. sordidus. Moreira et al (2017) concluded that the biological control of C. sordidus with the fungus B. bassiana was more effective than with Metarhizium Anisopliae, especially at the concentration of 20 g L-1. However, the producer needs to be aware that its application should begin before the pest is established in the crop.…”
Section: Introductionmentioning
confidence: 99%
“…The use of systemic insecticides is considered one of the main forms of control for this pest [3]. However, one of the major problems encountered in chemical control is the translocation of the active ingredient of these insecticides via sap to the fruits, which are mostly marketed "in natura" [4]. In this context another form of control which has been widely used is the use of attractive baits, produced with pieces of pseudostem split in half.…”
Section: Introductionmentioning
confidence: 99%
“…Sorokin have been shown to be the most promising biocontrol agents against BRB due to their cosmopolitan distribution and high lethality caused by their production of mycotoxins and growth which blocks the insect's digestive tract (TINZAARA et al 2015, SALUSTINO et al 2019). These species are reported to cause infections for more than 300 species of pest insects (MOREIRA et al 2017), which implies that this high genetic variability should be studied in order to select efficient entomopathogenic fungi adapted to the conditions where it is necessary to control BRB. Furthermore, the discovery of new native isolates with high virulence and infectivity can add value to biological control methods by reducing production costs and the use of conventional insecticides in banana fields (MEMBANG et al 2020).…”
mentioning
confidence: 99%